Strategi Pembudayaan Karakter Pada Pendidikan Dasar Islam - Yuni Masrifatin (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2019)
The learning process is essentially the process of contraction between students and educators, which is carried out consciously and planned, in order to develop the potential of their students in a more optimal direction. The character acculturation strategy must refer to several main principles, namely: Principles oriented to planned educational goals, Principles oriented to Individuality in arousing and developing each individual student, Intractive principle between student relationships and educators, Inspiring process so that students try and do something, the principle of student motivation, the principle of fun (enjoy) and not scare the students, the principle challenges students to develop the ability to taste and ratio in a balanced manner.